Optimalisasi Penyusunan Rencana Pelaksanaan Pembelajaran (RPP) Melalui Pelatihan Bagi Kelompok Kerja Guru Pendidikan Agama Islam Kecamatan Baso - Bambang Trisno; Lainah Lainah (Jurnal Dedikasia : Jurnal Pengabdian Masyarakat, 2022)
Indonesia is intensively innovating in the world of education. Freedom to learn has become an innovation that has been hotly discussed since 2019. One of the updated policies in the independence of learning is the teacher's lesson plan.  Through independent learning the lesson plans which previously consisted of hundreds of pages were  made slimmer, namely one sheet. This curriculum is very effective and efficient, Some elementary schools in the Baso Agam sub-district are not ready to implement this curriculum and most teachers do not understand the form of one-sheet lesson plans  applied explicitly  to elementary schools. The purpose of this activity is to optimize the strengthening of teacher pedagogic competencies in implementing the independent learning curriculum at the Baso PAI KKG. The action was carried out using the training method. This training activity positively impacts Baso PAI KKG teachers, teachers are more ready to implement the free learning curriculum and teachers' academic  competence in the lesson plands for free learning is more optimal. Because 28.6% chose very well, 55.4% chose a good level of understanding of the training on preparing 1 sheet lesson plans, and 58.9% said they were able to, and 26.8% said they were very able to explain it back to other teachers.